Chronic renal failure of unknown origin is caused by HNF1B mutations in 9% of adult patients: A single centre cohort analysis. Issue 4 (April 2014) - Musetti, Claudio; Quaglia, Marco; Mellone, Simona; Pagani, Alessia; Fusco, Ileana; Monzani, Alice; Giordano, Mara; Stratta, Piero
Abstract Background HNF1B gene mutations might be an underdiagnosed cause of nephropathy in adult patients mainly because of their pleomorphic clinical presentations. As most studies are based on paediatric populations, it is difficult to assess the likelihood of finding HNF1B mutations in adult patients and consequently define clinical settings in which genetic analysis is indicated. The aim of this study was the search for mutations in the HNF1B gene in a cohort of unrelated adult patients with nephropathy of unknown aetiology. Methods Patients were tested for the HNF1B gene if they had chronic kidney disease of unknown origin and renal structure abnormalities (RSA) or a positive family history of nephropathy. The HNF1B coding sequence and intron–exon boundaries were analysed by direct sequencing. The search for gene deletions was performed by Multiple Ligation Probe Analysis (MLPA). Results Heterozygous mutations were identified in 6 out of 67 screened patients (9.0%) and included two whole gene deletions, one nonsense (p.Gln136Stop), two missense (p.Gly76Cys and p.Ala314Thr) mutations and a frameshift microdeletion (c.384_390 delCATGCAG), the latter two (c.384_390 del and p.Ala314Thr) not ever being reported to date. Mean age of the mutated patients at screening was 48.5 years with a M/F ratio of 2/4. The clinical manifestations of affected patients were extremely pleomorphic, including several urological and extra‐renal manifestations. Conclusions Mutations of HNF1B could explain chronic kidney disease in up to 9% of adult patients with a nephropathy of unknown aetiology and RSA: therefore an HNF1B mutation analysis should be considered in this group of patients.